Cardiovascular Effect of Physical Exercise on Primary Sjogren's Syndrome (pSS): Randomized Trial - Garcia, Ana Beatriz Andrêo; Dardin, Luciana Paula; Minali, Paulo Alexandre; Trevisani, Virginia Fernandes Moça (Frontiers in Medicine, 2021)
Objective: To evaluate the effects of an exercise program on aerobic capacity, echocardiographic parameters, metabolic profile, quality of life and safety in patients with primary Sjogren's syndrome in a randomized trial. Methods: 60 women with pSS were evaluated from the SF-36 Short-Form Health Survey (SF-36) and EULAR Sjögren's Syndrome Disease Activity Index (ESSDAI) questionnaires. The participants performed ergospirometry and echocardiography; blood samples were collected to evaluate the metabolic profile. Patients were randomly divided into 2 groups: a training group that participated in the supervised training program and a control group. All variables were analyzed at baseline and after 28 weeks for both groups and we performed an intention-to-treat analysis. The training program consisted of 16 weeks of resistance exercises and, after, the exercise became aerobic. Patients and coaches were not blinded, contrary to the evaluators of all examinations/procedures and data analysts. Statistical analysis included Wilcoxon's rank sum test, chi-square test, and ANOVA test. P values < 0.05 were considered to be statistically significant. Results: The 2 groups were homogeneous at baseline. The training group showed a significant improvement in oxygen maximum volume (VO2max) and anaerobic threshold (AT). Comparison of the training group and control group after 28 weeks showed a significant difference relating to VO2max and in AT. We did not find statistically significant diference in echocardiographic parameters, metabolic profile and in questionnaires SF-36 and ESSDAI. Conclusions: This study showed significant improvement in aerobic capacity and glycated hemoglobin after a supervised training program in patients with pSS with safety.